The Southern slow cooker : big-flavor, low-fuss recipes for comfort food classics - Morris, Kendra Bailey (Ten Speed Press, 2013)
" A collection of 60 soulful, comforting, and wonderfully convenient recipes for Southern favorites--from Black Eyed Peas with Stewed Tomatoes to Country-Style Pork Ribs to Molasses Gingerbread. Few cuisines are more perfectly suited to low and slow cooking in a Crock-Pot than Southern food. Filled with rich braises, decadent gravies, and fall-apart tender pork and beef, The Southern Slow Cooker showcases the very best that Southern cooking has to offer--and demonstrates how easy it can be to make at home. Even the busiest home cooks will love Kendra Bailey Morris's simple and convenient recipes. With hardly any active cooking time and featuring inexpensive ingredients, each one results in deeply flavorful, satisfying food that will have you and your family asking for seconds. "--